Caries prevalence and associations with medications and medical comorbidities. (15th November 2018) - Jurasic, M. Marianne; Gibson, Gretchen; Wehler, Carolyn J.; Orner, Michelle B.; Jones, Judith A.
Abstract: Objectives: To use extensive electronic dental, medical, and pharmacy databases to estimate the prevalence of dental caries in a cohort of new patients during a 5‐year period (FY2010–FY2015) and determine whether medication use and medical comorbidities are associated with caries prevalence. Methods: This was a retrospective analysis of existing data from the Department of Veterans Affairs (VA). The number of teeth treated due to a caries‐related diagnosis was determined and outcomes were presented as number of teeth/person and proportion of patients receiving caries‐related treatment. Logistic and negative binomial regression modeled teeth/person with caries‐related treatment; covariates included age, gender, race, ethnicity, physical and mental comorbidities, and use of prescription medications and prescription drugs with strong anticholinergic properties. Results: The study population included 95, 850 dentate dental patients: 92.1 percent were male, mean age of 58.7 ± 12.6 years, 73.2 percent were White/Caucasian, and 21.3 percent were Black/African American. They were taking a mean of 10.6 ± 5.9 VA prescription drug classes, 0.6 ± 0.4 drugs with strong anticholinergic properties, and had 3.6 ± 2.2 physical and 1.4 ± 1.2 mental comorbidities. On average, 2.2 teeth/person received caries‐related treatment and 58 percent of the study population received any caries‐related treatment. An increase in the rate of caries‐related treatment in Veterans was statistically significantly associated with increased prescription medication use; one or more drugs with strong anticholinergic properties and with 1+ mental comorbidities. Increased physical comorbidity was not statistically significantly associated with caries‐related treatment. Conclusions: This study demonstrates a high prevalence of caries among Veteran dental patients, with an increased prevalence in those taking higher numbers of prescription medications.